PENGARUH PROFITABILITAS DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DEVIDEN SEBAGAI VARIABEL INTERVENING (STUDI EMPIRIS PADA PERUSAHAAN SUB. SEKTOR PROPERTY & REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012 – 2016) - Leang Andriani (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this research is to find the influence between profitability and sales growth, to firm value with dividend policy as intervening variable, at sub company. Property sector in IDX 2008-2012. Profitability using PBV, Growth penjulan using SG Dividend Policy using DPR Corporate value using PBV. The sampling technique used is purposive sampling. From the research results show that. (1) There is no positive effect of profitability on dividend policy, (2) There is no positive effect of sales growth on dividend policy, (3) There is no positive influence of dividend policy toward firm value, (4) there is positive influence of profitability to company value, (5) there is positive effect of sales growth to company value.